Corporate Financial Performance: is There Any Relationship with Covid-19? - Nelly Masnila; M. Husni Mubarok; Trizaurah Armiani (International Journal Labs, 2023)
The research was conducted to determine the impact of the COVID-19 pandemic on companies listed on the Indonesia Stock Exchange. The population in this study is a transportation company listed on the IDX. The data collected for processing are data on the financial ratios of transportation companies for a period of 4 years, namely 2 years before the pandemic (2018-2019) and data for 2 years when the pandemic occurred (2020-2021). The data analysis used in this study used descriptive analysis and comparative test models. The comparison test was performed using t-paired samples and Wilcoxon tests with the help of the program of the view. The results showed that although there were differences in the financial ratios of transportation companies before and during the Covid-19 pandemic, the results of the comparison test showed that there were no significant differences in the company's current ratio (liquidity ratio), solvency ratio (Solvability ratio), and profitability ratio (profitability ratio) before and during the Covid-19 pandemic. For the activity ratio, there is a significant difference in the ratio of receivable turnover (RTO) and asset turn ver (ATO), while fixed asset turnover (FATO) and working capital turnover (WCTO) show no significant difference.